1994
DOI: 10.1109/20.305629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of controlled carbon impurities on J/sub c/ in Ag/Bi(2223) tapes

Abstract: Abstrad-An extensive study of the detrimental effect of C on critical current densities (ic) of Ag sheathed Bi(2223) tapes has been carried out. High j, can only be obtained if the C content is kept to a minimum. Successive calcination steps at 820°C are effective in reducing the amount of C in the resulting powders. On the other hand, high energy milling increases the amount of C in the powder. Controlled quantities of C impurities were introduced into the powders by performing the calcinations in a CO, rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
8
1
Order By: Relevance
“…In contrast to the data of Flükiger et al [8], Seibt et al [9] and Jeremie et al [10,11] no carbon-rich phases were observed at 2212 grain boundaries after annealing at high CO 2 partial pressures. This is probably due to the fact that they investigated powder samples whereas, in this work, bulk materials were studied [8][9][10][11].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…In contrast to the data of Flükiger et al [8], Seibt et al [9] and Jeremie et al [10,11] no carbon-rich phases were observed at 2212 grain boundaries after annealing at high CO 2 partial pressures. This is probably due to the fact that they investigated powder samples whereas, in this work, bulk materials were studied [8][9][10][11].…”
Section: Discussioncontrasting
confidence: 70%
“…In contrast to Hornung et al [7], Jeremie et al [10,11] observed a decrease of the partial melting temperature for carbon-rich samples. Jeremie et al also studied the influence of the CO 2 partial pressure on the phase distribution in the calcined powders.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…2 shows that the average of particle size is about 1 μm. Further, The studies have shown that the critical current density is strongly influenced by C content in the precursor powder, and highest J c can be obtained with the C content below 200 ppm [6]. In order to decrease the C content, the precursor powder was annealed at 820 ºC for 2 h with flowing oxygen atmosphere after all calcination steps.…”
Section: Results and Discussmentioning
confidence: 99%
“…6. In general, the bubbling phenomenon occurs during heat treatment (sintering) or in service because it is mainly related to carbon content of the powder and joule heat, resulting in the degradation of both electrical properties and mechanical integrities [10], [11]. It seems that the bubbling of the jointed tape is related to the exposure of the core to liquid nitrogen at the end of joined region.…”
Section: Resultsmentioning
confidence: 99%